SIGNIFIED AND SIGNIFIER ON MORALITY MEANING IN “MEMBASUH” SONG LYRICS BY HINDIA FT. RARA SEKAR - Yuani Nurdwi Kaesari; Nur Sakinah, Myrna (Universitas Hasanuddin, 2023)
This article aims to analyze the moral meaning in the song lyrics of